Interfacial engineered gadolinium oxide nanoparticles for magnetic resonance imaging guided microenvironment-mediated synergetic chemodynamic/photothermal therapy. (October 2019) - Zhao, Zhenghuan; Xu, Kai; Fu, Chen; Liu, Heng; Lei, Ming; Bao, Jianfeng; Fu, Ailing; Yu, Yang; Zhang, Weiguo
Abstract: Engineering interfacial structure of biomaterials have drawn much attention due to it can improve the diagnostic accuracy and therapy efficacy of nanomedicine, even introducing new moiety to construct theranostic agents. Nanosized magnetic resonance imaging contrast agent holds great promise for the clinical diagnosis of disease, especially tumor and brain disease. Thus, engineering its interfacial structure can form new theranostic platform to achieve effective disease diagnosis and therapy. In this study, we engineered the interfacial structure of typical MRI contrast agent, Gd2 O3, to form a new theranostic agent with improved relaxivity for MRI guided synergetic chemodynamic/photothermal therapy. The synthesized Mn doped gadolinium oxide nanoplate exhibit improved T 1 contrast ability due to large amount of efficient paramagnetic metal ions and synergistic enhancement caused by the exposed Mn and Gd cluster. Besides, the introduced Mn element endow this nanomedicine with the Fenton-like ability to generate OH from excess H2 O2 in tumor site to achieve chemodynamic therapy (CDT). Furthermore, polydopamine engineered surface allow this nanomedicine with effective photothermal conversion ability to rise local temperature and accelerate the intratumoral Fenton process to achieve synergetic CDT/photothermal therapy (PTT). This work provides new guidance for designing magnetic resonance imaging guided synergetic CDT/PTT to achieve tumor detection and therapy. Graphical abstract: Image 1